Type 2 diabetes mellitus is associated with lower serum adiponectin level in Bangladeshi population (Mediscope, 2015)
The  aim  of  the  observational  case  control  study  was  to  find  out  the  association  of  type  2  diabetes  mellitus  (T2DM)  with  serum  adiponectin  level  in  Bangladeshi  population.  This  was  conducted  in  the  Biomedical  Research  Group,  Research  Division,  Bangladesh  Institute  of  Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM), Dhaka,  Bangladesh.  Sixty six T2DM subjects and seventy four healthy control subjects were included.  Diabetes  was  diagnosed  and  classified  as  per  World  Health  Organization  criteria.  Serum  adiponectin was measured by Enzyme Linked Immunosorbent Assay (ELISA) method. Serum  glucose  was  measured  by  glucose-oxidase  method;  serum  insulin  was  measured  by  chemiluminescence- based ELISA technique. The insulin secretory capacity (HOMA%B), insulin  sensitivity  (HOMA%S)  &  insulin  resistance  (HOMA-IR)  were  assayed  by  homeostasis  model  assessment method. Statistical analysis was performed using SPSS Windows version 11.5. The  median  (range)  fasting  serum  insulin  of  control  and T2DM subjects  were  14.7  (1.9-45.9)  and  18.1 (4.1-42.8), respectively. The median (range) serum adiponectin (?g/ml) of the control and  T2DM  subjects  were  8.7  (0.8-16.0)  and  6.2  (1.1-22.4).  The  serum  adiponectin  of  T2DM  was  significantly lower than the control subjects (p < 0.001). The median (range) HOMA%B values  of control and T2DM subjects were 160.1 (33.4-493.4) and 100.5 (17.7-349.3), respectively. The  median  HOMA%B  of  T2DM  subjects  was  significantly  lower  than  the  control  subjects  (p